Liver Transcriptomic Analysis of the Effects of Dietary Fish Oil Revealed a Regulated Expression Pattern of Genes in Adult Female Spotted Scat (Scatophagus argus) - Wang, Tuo; Jiang, Dongneng; Shi, Hongjuan; Mustapha, Umar Farouk; Deng, Siping; Liu, Zhilong; Li, Wanxin; Chen, Huapu; Zhu, Chunhua; Li, Guangli (Frontiers in Marine Science, 2021)
Despite the significance of n-3 LC-PUFA in fish oil in promoting the maturation of female broodstocks, the detailed mechanism of the effect on the expression of hepatic reproduction-related genes is still unclear. In this study, transcriptome sequencing was used to analyze the effect of higher dietary n-3 LC-PUFA level on gene expression in the liver of adult females spotted scat. Two-year-old female spotted scat (average weight, 242.83 ± 50.90 g) were fed with diets containing 8% fish oil (FO) or 8% soybean oil (SO) for 40 days. The fatty acid profile in the serum, liver and ovary was analyzed, and high proportions of n-3 LC-PUFA were observed in the FO group. The final average fish body weight and GSI were similar between FO and SO groups. The serum Vtg and HSI of the FO group were significantly higher and lower than that of the SO group, respectively. Comparatively, the liver transcriptome analysis showed 497 up-regulated and 267 down-regulated genes in the FO group. Among them, the expression levels of three estrogen-regulated genes (Vtga, Vtgb, and Zp4) were significantly higher in the FO than in the SO group. This expression pattern could be related to the up-regulation of Hsd17b7 (the key gene of liver steroid hormone synthesis) and the down-regulation of the Hsp90 (the estrogen receptor chaperone). The expression levels of Foxo1a and Lep, which are involved in the lipid metabolism, decreased significantly in the FO group, which may be related to the lower level of HSI in the FO group. The genes related to liver LC-PUFA absorption and transport, Fabp2 and Mfsd2ab, were significantly up-regulated in the FO group, indicating that fish actively adapt to high fish oil diets. Briefly, high fish oil diets can influence the expression of genes related to liver n-3 LC-PUFA metabolism and reproduction, inhibit liver fat accumulation, promote liver health and gonad development. This study will contribute to clarifying the mechanism of dietary n-3 LC-PUFA on promoting reproductive development in teleost fish.